2011
DOI: 10.1080/09540121.2011.613911
|View full text |Cite
|
Sign up to set email alerts
|

A qualitative study of barriers to consistent condom use among HIV-1 serodiscordant couples in Kenya

Abstract: This study explored barriers to consistent condom use among heterosexual HIV-1 serodiscordant couples who were aware of the HIV-1 serodiscordant status and had been informed about condom use as a risk reduction strategy. We conducted 28 in-depth interviews and 9 focus group discussions among purposively-selected heterosexual HIV-1 serodiscordant couples from Thika and Nairobi districts in Kenya. We analyzed the transcribed data with a grounded theory approach. The most common barriers to consistent condom use … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
0
4

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 20 publications
8
52
0
4
Order By: Relevance
“…Focus group discussions showed that male partners have a big influence on the adoption of most of the PHDP interventions including condom use and family planning. Condom use was seen as a result of unfaithfulness from the partner requesting its use, this finding corroborates with results from three different studies [14][15][16] which showed that male gender was reported to control the decision to use condom in sero-discordant relationship. Multiple Partnerships were also cited as a challenge affecting adoption of PHDP interventions, 28% of the respondents had other sexual partners of which 86.3% did not know the other partners HIV status, this agrees with results from a study done by Mac Kenzie that showed concurrent relationships contribute to spread of HIV [17] .…”
Section: Discussionsupporting
confidence: 81%
“…Focus group discussions showed that male partners have a big influence on the adoption of most of the PHDP interventions including condom use and family planning. Condom use was seen as a result of unfaithfulness from the partner requesting its use, this finding corroborates with results from three different studies [14][15][16] which showed that male gender was reported to control the decision to use condom in sero-discordant relationship. Multiple Partnerships were also cited as a challenge affecting adoption of PHDP interventions, 28% of the respondents had other sexual partners of which 86.3% did not know the other partners HIV status, this agrees with results from a study done by Mac Kenzie that showed concurrent relationships contribute to spread of HIV [17] .…”
Section: Discussionsupporting
confidence: 81%
“…Consistent with other studies, we found participants wanted to maintain their relationship and have a child or children together despite their or their partner's HIV status. [25][26][27][28][29][30] In our study, fully accepting the reality of being in a HIVserodiscordant couple was an important contextual element influencing fertility decision-making and timing of conception. Couples commonly wanted to have children in the near future when both partners were expected to be healthier and able to partake in childrearing.…”
Section: Discussionmentioning
confidence: 99%
“…And I can give birth to a child who doesn't have the virus.'' (HIV-infected female, age 26) Most HIV-uninfected partners expressed resounding acceptance of their partner's status. Knowledge and awareness of HIV as well as love and respect for their partner influenced HIV-uninfected partners' willingness to ''go on with life'' and ''accept each other'' following disclosure.…”
Section: Realizing Hiv-serodiscordancementioning
confidence: 99%
“…The results from a survey that was conducted in Uganda indicate that 61.8% of the surveyed men do not believe that discordant HIV results could exist between two partners in a committed relationship (Bwambale et al 2008). The qualitative literature includes numerous explanations from interviewees that reveal a belief that serodiscordance is impossible (Bunnell et al 2005;Bwambale et al 2008;Mlay et al 2008;Santow et al 2008;Ngure et al 2012). For example, in a study by Santow et al (2008), this belief is clearly evident in the following quote from a Malawian man:…”
Section: Testing Patterns and Empirical Factsmentioning
confidence: 77%